O papel da educação ambiental popular e da agroecologia na escola rural: estudando e aprimorando a formação socioambiental de professores(as) - Magri, Geisy Graziela (2012)
The field of environmental education is expanding and developing research focused on work with (the) teachers (the) students have a high profile over the years, emphasizing the importance of knowing (as) professionals involved in environmental education activities , their daily lives, their needs and difficulties. This study aims to analyze and understand the perceptions, values and environmental practices in the school environment through research critical of their effectiveness and trainer, through different stages of development, acting effectively and in forming and strengthening implementation of agroecology in daily life of rural schools and the adequacy of disciplinary curricula. The activities in this study were developed in a rural school, by performing a diagnosis, environmental education, which sought to investigate the perceptions and environmental practices developed; worked in construction, development and evaluation of a continuing education in environmental education and agroecology, developed in the unit HTPC in school schedules, coordinated the construction of an educational booklet with texts and methodologies of environmental education indicated by (the) teachers participating; encouraged and analyzed the development of environmental projects and presentation of the same Seminar on educational projects and environmental education rural schools - UFSCar. Through this study we can conclude that the effectiveness of the development of environmental education in the school environment depends on the formation of (the) teachers (as) active and transformations of concepts and teaching practices developed that seek to integrate educational practices, the reality Environmental and social and environmental training of students (as) and teachers (as). And from these activities can be transformative integrate agroecological knowledge with course content developed curricula learning, trying to teach (the) students (as) to rural work sustainably, recognizing the social, economic and cultural environment rural.